Routes of interaction across northern central Tigray (Ethiopia) between 2nd and 1st millennium BCE: Interdisciplinary research in the Rama area - Pfeiffer, Kristina; Hardt, Jacob; Breninek, Christopher; Nir, Nadav; Gerlach, Iris; Raue, Dietrich; Schütt, Brigitta (Journal of Global Archaeology, 2023)
We present the results of geographic-archaeological surveys and soundings that have been carried out in the Rama area of northern central Tigray between 2018 and 2019. This area so far received little attention despite its possible connecting function between the prominent pre-Aksumite sites of Yeha and its surroundings in Tigray and, e.g., the Sudanese Gash and Middle Nile regions. The special geographical setting and promising initial finds provided the base to investigate into forms of mobility and routes of interaction between the highland cultures of the northern Horn of Africa and the cultures of the middle Nile River, the northeastern Sudanese Gash Delta as well as parts of Egypt, especially between the 2nd and early 1st millennium BCE.